DIAGNOSTIC ACCURACY OF CONTRAST ENHANCED COMPUTED TOMOGRAPHY IN DIAGNOSING RENAL CELL CARCINOMA, TAKING HISTOPATHOLOGY AS GOLD STANDARD - Ayesha Munir (Army Medical College Rawalpindi, 2019)
Objective: To determine the diagnostic accuracy of contrast enhanced computed tomography (CECT) scan in detecting renal cell carcinoma taking histopathology as gold standard.